Bayesian Approach to Psychotherapy Integration: Strategic Modification of Priors - Krupnik, Valery (Frontiers in Psychology, 2019)
Integrative psychotherapies have become the mainstay in mental health care. The most researched therapy, CBT, being integrative itself, continues to integrate such new elements as mindfulness, spirituality, and experiential techniques. There is no commonly accepted strategy for psychotherapy integration. New elements are sometimes added on a trial and error basis with a following post-hoc theoretical and empirical justification. Other times, they are incorporated based on an ad-hoc theoretical premise, and empirical studies follow to support or invalidate it. Nevertheless, four main integrative strategies have been identified as technical eclecticism, common factors integration, principle-based assimilative integration, and theoretical integration (Norcross, 2005). Strategies outside of these four have also been suggested. Recently, a principle of nested hierarchy has been proposed as a way of integrating different strategies into a general roadmap for building an integrative therapy (Krupnik, 2018). The nested hierarchy principle does not, however, offer a strategy for theoretical integration at the top of its hierarchy. In this report, I suggest using the Bayesian theory of psychopathology for such strategy. I propose to apply Bayesian framework to psychotherapy integration and discuss a possibility of using it as a universal strategy called Strategic Modification of Priors (SMOP). I illustrate SMOP's application with a synopsis of a clinical case.